2015
DOI: 10.1007/s00360-015-0907-7
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue: physiological function and evolutionary significance

Abstract: In modern eutherian (placental) mammals, brown adipose tissue (BAT) evolved as a specialized thermogenic organ that is responsible for adaptive non-shivering thermogenesis (NST). For NST, energy metabolism of BAT mitochondria is increased by activation of uncoupling protein 1 (UCP1), which dissipates the proton motive force as heat. Despite the presence of UCP1 orthologues prior to the divergence of teleost fish and mammalian lineages, UCP1's significance for thermogenic adipose tissue emerged at later evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
204
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(214 citation statements)
references
References 250 publications
(231 reference statements)
6
204
1
3
Order By: Relevance
“…in lambs and rabbits it disappears several days 265 to month after birth (reviewed in (Oelkrug et al 2015). In humans, BAT was regarded to be 266 restricted to a short period after birth, but recently has been detected in adults using This fits to data in humans where no change in FGF21 was observed in hyperthyroidism or 381…”
Section: Thyroid Hormone-mediated Effects On Adipose Tissue 247supporting
confidence: 72%
See 1 more Smart Citation
“…in lambs and rabbits it disappears several days 265 to month after birth (reviewed in (Oelkrug et al 2015). In humans, BAT was regarded to be 266 restricted to a short period after birth, but recently has been detected in adults using This fits to data in humans where no change in FGF21 was observed in hyperthyroidism or 381…”
Section: Thyroid Hormone-mediated Effects On Adipose Tissue 247supporting
confidence: 72%
“…Non-shivering thermogenesis is mainly initiated by a cutaneous cold-sensation which 67 via cold sensitive thermoreceptors activates the sympathetic nervous system (SNS) 68 (Nakamura and Morrison 2008). Subsequently, the SNS stimulates the release of 69 noradrenaline from postganglionic sympathetic fibres and induces β3-adrenergic receptor 70 (ARβ3)-mediated pathways that activate lipolysis and the release of free fatty acids (FFA, 71 reviewed in (Oelkrug, et al 2015)). FFA stimulate mitochondrial energy dissipation by 72 activation of the uncoupling protein 1 (UCP1) in the inner mitochondrial membrane.…”
Section: Components Of Thermoregulation 44mentioning
confidence: 99%
“…β‐3 Adrenergic stimulation activates cellular adenylyl cyclase, which leads to the conversion of adenosine triphosphate (ATP) to cyclic adenosine monophosphate (cAMP), activation of protein kinase A, and phosphorylation and activation of triacylglycerol lipase. The phosphorylated lipase converts triacylglycerols (white storage fat) into free fatty acids, which act to release uncoupling protein 1 (UCP1) by overriding the inhibition caused by purine nucleotides (adenosine diphosphate (ADP), guanosine diphosphate (GDP), and adenosine triphosphate (ATP)) (Oelkrug et al , 2015). The UCP1‐mediated uncoupling of the respiratory chain in mitochondria ultimately produces the metabolic heat or thermogenesis (Fedorenko et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the adipose tissue is not simply a deposit of lipids for energy storage but also interacts with other organs through secretion of adipokines and free fatty acids (FFA) [3]. Moreover, different types of adipocytes have been identified: white (WAT), brown (BAT) and the recently discovered beige (BeAT) [4], [5], [6]. The main characteristic of the brown and beige adipocytes is the presence of mitochondria and the possibility of fat burning with the production of heat (i.e.…”
Section: Introductionmentioning
confidence: 99%